2010
DOI: 10.1002/tcr.200900025
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of (+)‐vinblastine: Control of the stereochemistry at C18′

Abstract: Vinblastine has been widely known as a prominent agent in cancer chemotherapy, and in order to search for more potent drugs, various analogs have been derived from natural products. However, because modifications of natural products have limited classes of derivatives, an efficient synthetic route toward vinblastine has been required.Herein a stereocontrolled total synthesis of (+)-vinblastine is described. The synthesis of the upper half features a stereoselective construction of the tertiary alcohol through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
(28 reference statements)
0
9
0
Order By: Relevance
“… 417 Individually, researchers at Eli Lilly demonstrated that extracts of Catharanthus roseus influenced activity against P-1534 leukemia in mice, and also extracted vinblastine as a potent unit in 1959. 418 In 2010, Yokoshima et al reported 419 a stereocontrolled total synthesis of (+)-vinblastine (514). The synthesis of the upper half specifies the stereoselective formation of the tertiary alcohol via a 1,3-dipolar cycloaddition of nitrile oxide and a Baeyer–Villiger oxidation, a simple indole construction using the radical cyclization of o -alkenylthioanilide, and also the macrocyclization of 2-nitrobenzenesulfonamide.…”
Section: Miscellaneousmentioning
confidence: 99%
See 1 more Smart Citation
“… 417 Individually, researchers at Eli Lilly demonstrated that extracts of Catharanthus roseus influenced activity against P-1534 leukemia in mice, and also extracted vinblastine as a potent unit in 1959. 418 In 2010, Yokoshima et al reported 419 a stereocontrolled total synthesis of (+)-vinblastine (514). The synthesis of the upper half specifies the stereoselective formation of the tertiary alcohol via a 1,3-dipolar cycloaddition of nitrile oxide and a Baeyer–Villiger oxidation, a simple indole construction using the radical cyclization of o -alkenylthioanilide, and also the macrocyclization of 2-nitrobenzenesulfonamide.…”
Section: Miscellaneousmentioning
confidence: 99%
“…The synthesis of the lower half was achieved using a Mitsunobu coupling reaction of indole 505 (prepared from 7-mesyloxyquinoline (503) in seven steps) and 2,4-dinitrobenzenesulfonamide (chiral amine) 506 (prepared from 2-pentenal (504) in six steps), which after over three steps afforded vindoline (507). 419 On the other hand, the upper unit 511 was synthesized from n -butyraldehyde (508) and after 16 steps gave the alkenylthioanilides 509. Then, numerous conditions were examined, and it was found that using THF as a solvent inhibited the isomerization to provide indole 510 in a satisfactory yield (67% yield).…”
Section: Miscellaneousmentioning
confidence: 99%
“…Monoclonal antibody after peptide-based vaccines are the second largest classes of therapeutic proteins agents have been approved by the Food and Drug Administration for use in humans [11,12] Antibodies against the extracellular region of HER receptor could inhibit kinase signaling pathway through induction of immunological response and subsequent internalization of HER receptor [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Among the plant-based drugs approved, or with clinical trials launched in the period from 2000 to 2010, terpenoid-related compounds are dominated by only three scaffolds: Taxol (or paclitaxel), artemisinin, and vinblastine [14,88,103]. The key for the successful development of these scaffolds in clinical applications and establishment as treatment has been securing supply of the compounds through intense efforts in biotechnology or semi-or full chemical synthesis [23,93,128].…”
Section: Introductionmentioning
confidence: 99%